TechLab and Alexon Giardia Enzyme-Linked Immunosorbent Assay Kits Detect Cyst Wall Protein 1 - Boone, James H. (American Society for Microbiology, 1999)
A Giardia lamblia antigen detected by the TechLab Giardia Test (TechLab, Inc., Blacksburg, Va.) and the Alexon ProSpecT Giardia microplate assay (Alexon, Inc., Sunnyvale, Calif.) was purified by immunoaffinity chromatography from supernatant fluids of encystment cultures. Two major proteins (M(r) 22,000 and 26,000) were observed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Coomassie staining that did not resemble the GSA65 antigen reportedly detected by the Alexon test. These proteins reacted intensely with the monoclonal antibodies used in both commercial enzyme-linked immunosorbent assays (ELISAs). Both proteins had identical N-terminal amino acid sequences and were identified as cyst wall protein 1 (CWP1). The 26-kDa form appeared early during encystment followed by the appearance of the 22-kDa form. Recombinant CWP1 (M(r) 26,000) was strongly positive in both commercial tests. CWP1 was stable in human stool specimens, resistant to degradation by proteases and N- and O-glycanases, and unaffected by oxidation with sodium periodate. Two minor proteins with M(r)s of 32,000 and 39,000 were detected in CWP1 preparations by using a sensitive fluorescent protein stain. Both were identified as CWP2, and neither reacted with the monoclonal antibodies from the commercial tests. We analyzed 535 stool specimens for CWP1 by using both commercial ELISAs and resolved discrepant results by using routine ova and parasite examination (O&P) and on immunofluorescence antibody assay. The presence of CWP1 correlated well between both ELISAs (98.7% correlation). Our results demonstrate that both commercial ELISAs detect CWP1, which is a useful diagnostic marker because it is highly stable, is secreted in large amounts by encysting trophozoites, and correlates well with O&P.